ANALISIS KESALAHAN SISWA KELAS VIII SMP NEGERI 6 PALU DALAM MENYELESAIKAN SOAL AKM DITINJAU DARI KEMAMPUAN MATEMATIKA - Fasya Ardhinda Anatasya; Ibnu Hadjar; Baharuddin Paloloang; Fajriani Fajriani (Universitas Tadulako, 2025)
This study aims to obtain the results of error analysis of 8th grade students of SMP Negeri 6 Palu in terms of mathematics ability with high, medium and low ability categories in solving AKM problems. The subjects of this study were 3 students of class VIII SMP Negeri 6 Palu who were selected based on the category of mathematical ability level. The type of research used was descriptive with a qualitative approach Students' errors were analyzed using Newman's procedure which includes five categories of errors: reading, comprehension, transformation, process skills and encoding. Data were obtained through AKM numeracy level 4 written test and in-depth interviews. Based on the results of the research and discussion, it can be concluded several things. namely: (1) none of the subjects made reading errors, because when asked to read the problem all subjects could read the problem properly (2) none of the subjects made comprehension errors, this can be seen during the written test and interview that all subjects can explain the important information contained in the problem and can explain what is asked in the problem (3) transformation errors were made by all research subjects, because the three subjects could not use the appropriate problem solving method. (4) process skill errors were made by all research subjects, because the three subjects were mistaken in operating the problem or incorrect in performing calculations (5) encoding errors were made by all research subjects, because the three subjects were wrong in writing the results or did not write the final result of the answer.